Limitations of a Single-Item Assessment of Suicide Attempt History: Implications for Standardized Suicide Risk Assessment - Hom, Melanie A. (Psychol Assess, 2015)
Although a suicide attempt history is among the single best predictors of risk for eventual death by suicide, little is known about the extent to which reporting of suicide attempts may vary by assessment type. The current study aimed to investigate the correspondence between suicide attempt history information obtained via a single-item self-report survey, multi-item self-report survey, and face-to-face clinical interview. Data were collected among a high-risk sample of undergraduates (N = 100) who endorsed a past attempt on a single-item prescreening survey. Participants subsequently completed a multi-item self-report survey, which was followed by a face-to-face clinical interview, both of which included additional questions regarding the timing and nature of previous attempts. Even though 100% of participants (n = 100) endorsed a suicide attempt history on the single-item prescreening survey, only 67% (n = 67) reported having made a suicide attempt on the multi-item follow-up survey. After incorporating ancillary information obtained from the in-person interview, 60% of participants qualified for a CDC-defined suicide attempt. Of the 40% who did not qualify for a CDC-defined suicide attempt, 30% instead qualified for no attempt, 7% an aborted attempt, and 3% an interrupted attempt. These findings suggest that single-item assessments of suicide attempt history may result in the misclassification of prior suicidal behaviors. Given that such assessments are commonly used in research and clinical practice, these results emphasize the importance of utilizing follow-up questions and assessments to improve precision in the characterization and assessment of suicide risk.